Peran Guru dalam Pembelajaran pada Siswa Sekolah Dasar - Dea Kiki Yestiani; Nabila Zahwa (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2020)
Lack of understanding of children's learning can be caused by several factors. One of them is the lack of teacher's role in the learning process at school can cause children's understanding to decrease, especially in elementary school children. The role of teachers in primary schools is still very much needed because elementary school children still lack the comprehension of what they see and hear. With this phenomenon, research is conducted to find out how the role of teachers in learning in schools among elementary school students.